2018
DOI: 10.1016/j.schres.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Autism and psychosis: Clinical implications for depression and suicide

Abstract: There is increasing recognition of the co-occurrence of autism and schizophrenia spectrum disorders. However, the clinical significance of this on outcomes such as depression and suicidal thinking has not been explored. This study examines the association of autism spectrum traits, depressive symptoms and suicidal behaviour in individuals with psychotic experiences. In two cross sectional studies, individuals from a non-help seeking university student sample and patients with first episode psychosis (FEP) serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 42 publications
5
35
1
1
Order By: Relevance
“…CAPEp and CESD-R measures appeared consistent with previous findings (Ruzich et al, 2015;Upthegrove et al, 2018;Van Dam & Earleywine, 2011), levels of self-harm and suicidality were both higher in our sample than in previously published data (Meltzer H, 2002), which may have biased our results. Finally, traits and symptoms in our study were measured at one time-point only.…”
Section: Strengths and Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…CAPEp and CESD-R measures appeared consistent with previous findings (Ruzich et al, 2015;Upthegrove et al, 2018;Van Dam & Earleywine, 2011), levels of self-harm and suicidality were both higher in our sample than in previously published data (Meltzer H, 2002), which may have biased our results. Finally, traits and symptoms in our study were measured at one time-point only.…”
Section: Strengths and Limitationssupporting
confidence: 91%
“…For example, studies found that co-occurrence of autistic and psychotic traits was associated with less impaired executive and social functioning in undergraduate students in China (Shi et al, 2017), and better perspective taking abilities in university students in the UK (Abu-Akel, Wood, Hansen, & Apperly, 2015). On the other hand, a study involving 381 university students undertaken in the UK suggested that co-occurrence of autistic and psychotic traits was associated with significantly increased levels of depression (Upthegrove et al, 2018). The conduct of these studies in student populations may limit the applicability of their findings to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies included only children and adolescents (18, 38, 39). Four studies were undertaken in Japan (36, 37, 42, 45), four in Europe (35, 40, 41, 46), three in the U.S. (18, 39, 43), and two in China (38, 44). Most of the studies included a high percentage of males, with the exception of three studies (40, 42, 45).…”
Section: Resultsmentioning
confidence: 99%
“…Self-reported autistic traits measured by the AQ accurately distinguish over 80% of autistic and non-autistic people (Baron-Cohen et al 2001) and predict who will later go on to obtain a diagnosis of autism (Woodbury-Smith et al 2005). However, self-reported autistic traits are also elevated in a number of other groups, such as those with psychosis (Upthegrove et al 2018) and borderline personality disorder (Dudas et al 2017). Hence, some have argued that the AQ does not specifically measure autistic traits, but more general social skills and social interest, regardless of the underlying condition (Lugnegård et al 2015).…”
Section: Discussionmentioning
confidence: 99%